2021
DOI: 10.1186/s13071-021-05081-x
|View full text |Cite
|
Sign up to set email alerts
|

Aedes albopictus life table: environment, food, and age dependence survivorship and reproduction in a tropical area

Abstract: Background Environmental conditions affect the biology of mosquito vectors. Aedes albopictus is a major vector of many important diseases including dengue, Zika, and chikungunya in China. Understanding the development, fecundity, and survivorship of Ae. albopictus mosquitoes in different environmental conditions is beneficial for the implementation of effective vector control measures. Methods Aedes albopictus larval and adult life-table experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The feature selection was based on the biological and environmental dependencies of the mosquito life cycle, as temperature, precipitation, and relative humidity directly affect the reproduction, development, and the survival of Ae. albopictus [ 69 ]. Day length has been demonstrated to also affect the life cycle of the mosquito [ 70 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…The feature selection was based on the biological and environmental dependencies of the mosquito life cycle, as temperature, precipitation, and relative humidity directly affect the reproduction, development, and the survival of Ae. albopictus [ 69 ]. Day length has been demonstrated to also affect the life cycle of the mosquito [ 70 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…The datasets were observed in 9 replicates. Practical procedures were followed from Aida et al (2011) and Cui et al (2021) for study.…”
Section: Laboratory Rearing Proceduresmentioning
confidence: 99%
“…Several studies have found that there are variations in life history traits such as larval development and survival in Ae. aegypti in different areas ( Bong et al, 2021 ; Cui et al, 2021 ). This is because different areas may have diverse environmental conditions which may affect larval development, survival and adult emergence ( Afrane et al, 2008 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%